Pathophysiological mechanisms of gestational hypertensive syndromes (Research, Society and Development, 2023)
Pregnancy-specific hypertensive disease (GHD) is one of the most common complications of pregnancy. Although the prognosis is favorable in mild cases, its more severe forms, such as eclampsia and HELLP syndrome, are the main causes of maternal and perinatal morbidity and mortality, being responsible for 15% of maternal deaths in the United States of America (USA) and even higher figures in developing countries. Although the course of DHEG begins at the time of placentation, clinical manifestations are generally late, that is, they occur in the last trimester of pregnancy. However, when these manifestations appear at early gestational ages, they are directly related to worse maternal and perinatal outcomes, and should alert to the presence of high blood pressure prior to pregnancy, thrombophilia or pre-existing kidney disease. The only exception is gestational trophoblastic disease, which may be associated with DHEG in early pregnancy.